(untitled) (Research, Society and Development, 2022)
The first edition of the Olympic Games in South America raised several focuses of investigation, among them the segment of artistic shows, called opening and closing ceremonies. Those events are responsible for the largest audiences within the Olympic mega-event and serve as identity flag-bearers for the host nation. This study launched itself into decoding symbologies of Brazilian national identity in the artistic show of the Closing Ceremony of the Rio 2016 Olympic Games, through the lens of the “Moving Images Analysis” method based on the epistemology of the Peircean semiotics. An exploratory and descriptive qualitative approach was used, based on bibliographic and documental surveys. The results indicate that the closing ceremony traversed through Brazilian art in its multiple forms, from cave paintings and engravings, indigenous handicrafts, European cultural heritages, to contemporary artists such as Roberto Burle Marx. The show also has a greater range of attributes of national identity in the sound segment when compared to the opening ceremony, including musical rhythms such as carnival marches, maxixe, xaxado, indigenous tunes and classical music.